Lactobacillus infection related to midgut protein synthesis in the dengue vector Aedes albopictus: Platform of non-symbiont bacteria for the control of Aedes vectors - Hamady, Dieng; Parimal, Talukder; Tomomitsu, Satho; Yukihiko, Nakashima; Nobuhiro, Kashige; Ikenna N., Nwachukwu; Adzitey, Frederick; Rahman G. M., Saifur; Che Salmah, Md Rawi; Abu Hassan, Ahmad; Fumio, Miake (JPVB, 2010)
There have been a number of recent studies regarding the use of engineered insect symbiont bacteria for control of insect-borne diseases. However, searches for cultivable bacteria residing in the mosquito midgut have met with little success. The present study was conducted to evaluate the effects of the human non-pathogenic lactobacilli on midgut protein synthesis in the dengue vector Aedes albopictus, taking into account the ease of infection and its persistence. It was showed that antibiotic treatment of mosquitoes did not prevent experimental infection, and readily reduced undesired infection, but did not prevent re-infection by Lactobacillus spp. It suggests a high potential of colonization of a target vector population under field conditions. Ingested lactobacilli remained in the female midgut for five days. Lactobacillus reuteri (Lactobacillales: Lactobacillaceae) showed more specific proteins than Lactobacillus brevis (Lactobacillales: Lactobacillaceae). Some proteins identified in L. brevis were present at much higher levels in L. reuteri, while other proteins found in the latter were found at higher levels in the former. Infection by L. brevis resulted in the absence of many proteins. In contrast, L. reuteri infection resulted in increased levels of synthesis of a set of proteins present in the healthy midguts. Both bacteria triggered changes in midgut protein synthesis, but activation was seen to a greater extent with L. reuteri. These results are discussed in the context of paratransgenesis.